Analysis of Fishing Ground Surface Gill Net Bogak Besar Waterway Noni District of Teluk Serdang Bedagai North Sumatra Province - Aprianto Manalu; Usman '; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research about Fishing Ground Gill Net Surface in the waters of theBogak Besar Noni Teluk Serdang Bedagai North Sumatra Province held on 23August 2014. The aimed of this to determine the state of the marine environmentoperation of gill nets surface such as depth, brightness, flow velocity, temperature,salinity, pH, and the type of fish caught in the waters of the Great Bogak. Themethod used in this study is a survey method that is by measuring the directobservation of environmental parameters and operation of a surface gill netfishing gear research location. The data collected in this study are: demography,topography, depth, brightness, temperature, salinity, current velocity, and pH. Thecatch and the measurement of these parameters are collected and then tabulatedinto a table and analyzed descriptively.The observation of environmental parameters during the study was thetemperature ranges from 28 0C - 30 0C, Flow ranges from 0.15 m / s - 0.25 m / s,the brightness ranging from 0.80 m - 1.13 m, Kedalama ranged between 10 m - 16m, salinity ranged between 23.4‰- 26.2‰and pH (acidity) ranged from 7-9.Keywords: Gill net, gill net operating area